A Basic Guide to Bobsledding - Kummer, Hans. (Milwaukee, WI Gareth Stevens Publishing, 2002)
A Basic Guide to Bobsledding offers a clear, concise introduction to one of the most challenging and technically advanced of all Olympic events.
5 - 9
Keywords: Bobsledding; Olympics